Pelatihan Job Crafting Sebagai Solusi Meningkatkan Keterikatan Kerja Karyawan Perusahaan Finansial Teknologi - Aprilinda, Lia; Sahrah, Alimatus (Psikostudia : Jurnal Psikologi, 2022)
Employees are expected to have work engagement to be able to increase good work productivity and be able to compete. This study aims to determine the effect of job crafting training to increase work engagement on employees of PT. STI. The subjects of this study were 20 employees divided by 10 employees in the experimental group and 10 employees in the control group randomly. The research method uses a quasi-experimental design with a pretest-posttest control group design. Job engagement was measured using the Utrecht Work Engagement Scale (UWES) and the Job Crafting Scale. The data analysis technique used independent sample t test and paired sample t test. From the results of the independent sample t test analysis, the t value was -3.227 (p <0.05) between the posttest average results of the experimental group of 56.9 and the control group's mean of 47.6. While the results of the analysis of the paired sample t test with a t value of -7.271 (p <0.05) with a pretest of 44.9 and a posttest of 56.9. This indicates that there is a significant difference in the scores between the pretest and posttest of the experimental group. This means that job crafting training is effective in increasing employee engagement. Karyawan diharapkan memiliki keterikatan kerja untuk dapat meningkatkan produktivitas kerja yang baik dan mampu bersaing. Penelitian ini bertujuan mengetahui pengaruh pelatihan job crafting untuk meningkatkan keterikatan kerja pada karyawan PT. STI. Subjek penelitian ini berjumlah 20 karyawan yang dibagi secara random dalam kelompok eksperimen dan kontrol. Metode penelitian menggunakan quasi eksperimen dengan desain pretes-posttest control group design. Keterikatan kerja diukur menggunakan Utrecht Work Engagement Scale (UWES) dan Job Crafting Scale. Teknik analisis data menggunakan independent sample t test dan paired sample t test. Dari hasil anlisis independent sample t test didapatkan nilai t sebesar -3,227 (p<0,05) antara hasil rerata posttest kelompok eksperimen sebesar 56,9 dengan rerata kelompok kontrol sebesar 47,6. Sedangkan hasil analisis paired sample t test dengan nilai t sebesar -7,271 (p<0,05) dengan pretest sebesar 44,9 dan posttest sebesar 56,9. Hal ini menunjukkan bahwa terdapat perbedaan nilai yang signifikan antara pretest dan posttest kelompok eksperimen. Hal ini berarti bahwa bahwa pelatihan job crafting efektif untuk meningkatkan keterikatan kerja karyawan.